Diaphragm for redox flow battery and manufacturing method thereof

The diaphragm for redox flow batteries, featuring a core material with a protective layer and ion exchange resin with metal sulfide compound support, addresses issues of proton permeability and handling, achieving high conductivity and low resistance with improved active material retention.

JP2025007439APending Publication Date: 2025-01-17NIDAIKI CO LTD +1

Patent Information

Application Number
JP2023108830
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Conventional diaphragms for redox flow batteries suffer from low proton permeability, high resistance, insufficient active material permeation blocking, and poor handling properties, leading to electrolyte leakage and reduced current efficiency.

Method used

A diaphragm composed of a sheet-like core material coated with a protective layer and laminated with an ion exchange resin containing porous inorganic particles supporting a metal sulfide compound, enhancing proton conductivity, permselectivity, and permeation blocking while allowing dry storage.

Benefits of technology

The diaphragm exhibits excellent proton conductivity, low internal resistance, effective active material retention, and improved handling properties, preventing electrolyte leakage and maintaining performance over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007439000001_ABST
    Figure 2025007439000001_ABST
Patent Text Reader

Abstract

To provide a diaphragm for a redox flow battery which has good proton conductivity, selective permeability, low internal resistance, excellent active material permeation prevention function, and good handleability.SOLUTION: A diaphragm 1 for a redox flow battery is configured such that the outside of a sheet-like core material B made of a polyester nonwoven fabric is covered with a protective layer Lp made of an acrylic water-absorbing polymer, and a resin film Li made of an ion-exchange resin (mainly composed of rosin and shellac resin) containing porous inorganic granules (diatomaceous earth) carrying a metal sulfide compound is laminated on the outside of the protective layer Lp.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a membrane used in a redox flow battery and a method for producing the same. [Background technology]

[0002] Redox flow batteries are known as large-capacity storage batteries. Redox flow batteries consist of a positive electrode and a positive electrode active material (vanadium V 4+ The cathode electrolyte (cathode cell) contains a negative electrode and a negative electrode active material (vanadium V 3+ The redox flow battery has a structure in which a negative electrode electrolyte (negative electrode cell) containing an electrolyte such as a positive electrode active material (such as a lithium ion battery) is separated by a diaphragm, and is configured to perform charging and discharging by utilizing the oxidation-reduction reaction of both positive and negative active materials. This type of redox flow battery is also suitable for large-scale use because it can be made large-capacity by distributing the electrolyte containing the active materials of both the positive and negative electrodes from a storage tank to an electrolytic cell.

[0003] The membrane of such a redox flow battery is required to prevent the electrolyte containing the active materials of both electrodes from mixing (to prevent the active materials contained in the electrolyte from permeating), to be resistant to oxidation, to have low electrical resistance, and to have good permeability to protons that carry electric charge. For this reason, as membranes for redox flow batteries, there have been proposed porous membranes made of polytetrafluoroethylene (PTFE), porous membranes made of polyolefin (PO)-based resins, and nonwoven fabrics of PO-based resins, as shown in Patent Document 1, a porous membrane made of PTFE with a porous structure formed therein, and a crosslinked polymer having an anion exchange group, as shown in Patent Document 2, and a membrane made of polysulfone-based resin as a hydrocarbon-based ion exchange resin, as shown in Patent Document 3. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-158383 A [Patent Document 2] Japanese Patent Application Publication No. 62-226580 [Patent Document 3] Japanese Patent Application Publication No. 6-188005 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the diaphragm made of a porous PTFE membrane as in Patent Document 1 and the diaphragm made of a composite of a crosslinked polymer having an anion exchange group and a porous PTFE membrane as in Patent Document 2 have problems such as low proton permeability, high internal resistance, insufficient function of preventing the permeation of active materials (function of preventing leakage of electrolyte), and poor current efficiency. On the other hand, the diaphragm made of a polysulfone resin as in Patent Document 3 has insufficient strength, so there is a risk that its performance will deteriorate due to factors such as swelling and shrinkage when it is used repeatedly in an electrolyte. In addition, the diaphragm made of a polysulfone resin as in Patent Document 3 loses its performance when it dries, so it must be stored in a wet state at all times and must be installed in a redox flow battery using a working pool or the like, which makes it difficult to handle.

[0006] An object of the present invention is to provide a diaphragm for a redox flow battery which overcomes the above-mentioned problems of the conventional diaphragms for redox flow batteries, has good proton conductivity and selective permeability, has low internal resistance, is excellent in preventing the permeation of an active material (function of preventing leakage of an electrolyte), and has good handleability. [Means for solving the problem]

[0007] Among the present inventions, the invention described in claim 1 is a diaphragm used in a redox flow battery, characterized in that a resin membrane made of an ion exchange resin containing porous inorganic granules supporting a metal sulfide compound is laminated on the outside of a sheet-like core material.

[0008] The invention described in claim 2 is characterized in that, in the invention described in claim 1, the ion exchange resin contains at least one of rosin or its modified substance, shellac resin, viscose, and cellulose.

[0009] The invention described in claim 3 is the invention described in claim 1, characterized in that the sheet-like core material is coated with a protective layer mainly composed of an acrylic water-absorbing polymer, and the resin film is laminated on top of the protective layer.

[0010] The invention described in claim 4 is the invention described in claim 1, characterized in that an intermediate coating made of a hydrophobic or water-resistant synthetic resin is formed between the protective layer and the resin film.

[0011] The invention described in claim 5 is the invention described in claim 1, characterized in that a surfactant is added to the ion exchange resin.

[0012] The invention recited in claim 6 is a method for producing a diaphragm for a redox flow battery, comprising the steps of: coating a sheet-like core material with a protective layer; and adhering an ion exchange resin containing porous inorganic granules supporting a metal sulfide compound to the sheet-like core material coated with the protective layer. Effect of the Invention

[0013] The redox flow battery membrane according to claim 1 (hereinafter simply referred to as the membrane) has good proton conductivity and selective permeability because the metal sulfide compound supported on the porous inorganic granules efficiently transfers protons. The membrane according to claim 1 also has very low internal resistance because the metal sulfide compound supported on the porous inorganic granules exhibits high electrical conductivity. Furthermore, the membrane according to claim 1 has excellent active material permeation prevention function, and can retain the sulfonating agent in a solidified state within the metal sulfide compound supported on the inorganic granules, allowing it to be stored in a dry state, and therefore has excellent handleability.

[0014] In the membrane described in claim 2, the ion exchange resin contains rosins, shellac resin, viscose, or cellulose, and has high adhesion to the core material and high retention of the porous inorganic granules carrying a metal sulfide compound. Therefore, even after long-term use, the ion exchange resin does not desorb from the core material and the porous inorganic granules do not desorb from the resin membrane, and good proton conductivity and selective permeability can be maintained.

[0015] The membrane described in claim 3 has a sheet-like core material coated with a protective layer mainly composed of an acrylic water-absorbent polymer, and a resin film laminated on the protective layer, which effectively prevents the sheet-like core material such as polyester nonwoven fabric from being eroded by the sulfonating agent held in the porous inorganic granules supporting the metal sulfide compound.

[0016] In the diaphragm according to claim 4, the protective layer covering the sheet-like core material is covered with an intermediate coating made of a hydrophobic or water-resistant synthetic resin, so that the protective layer is unlikely to leak (dissolve) into the electrolyte, and therefore it is possible to very effectively prevent the sheet-like core material from being eroded by the sulfonating agent held in the porous inorganic granules supporting the metal sulfide compound.

[0017] In the membrane according to claim 5, a surfactant is added to the ion exchange resin, so that the flexibility is not lost even when the membrane is stored for a long period of time after production.

[0018] According to the method for producing a diaphragm as set forth in claim 6, a diaphragm which has good proton conductivity and selective permeability, very low internal resistance, an excellent active material permeation blocking function, and excellent handleability can be produced easily and at low cost. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is an explanatory diagram showing an example of a redox flow battery in which a diaphragm is provided. [Diagram 2] FIG. 1 is an explanatory diagram showing a cell installed in a redox flow battery. [Diagram 3] FIG. 2 is an explanatory view showing a cross section of a diaphragm obtained in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The diaphragm according to the present invention is characterized in that a resin membrane made of an ion exchange resin containing porous inorganic particles carrying a metal sulfide compound is laminated on the outside of a sheet-like core material. As the core material (sheet-like core material) used for the diaphragm, a woven fabric (woven or knitted fabric), a nonwoven fabric, a net-like material, a porous sheet, etc. made of synthetic resins such as polyester, polyolefin, polyamide, etc., semi-synthetic resins, or natural resins can be suitably used. More specifically, a staple or short fiber made of polyester fiber, polyethylene fiber, polypropylene fiber, glass fiber, aramid fiber, polyamide fiber, other synthetic fibers, natural fibers such as hemp and pulp, or a mixed fiber thereof, a ceramic sheet, etc. can be suitably used. Among them, the use of a spunbond (nonwoven fabric) made of polyester is particularly preferable because the diaphragm has excellent strength.

[0021] Many of the above-mentioned core materials are corroded by the acid component of the electrode liquid, so in the diaphragm according to the present invention, the surface of the core material (surface of the constituent material) can be covered with a protective film to prevent damage to the core material by the electrode liquid. As a material for forming such a protective layer, acrylic resins, polyester resins, urethane resins, vinyl chloride resins, epoxy resins, melamine resins, fluorine resins, silicon resins, butyral resins, phenolic resins, vinyl acetate resins, or mixtures, copolymers, and modified products thereof, water-soluble resins, hydrophilic resins, and hydrolyzable organosilicon compounds such as alkoxysilanes, can be used alone or in combination of two or more. Among them, the use of acrylic water-absorbing polymers such as sodium polyacrylate is particularly preferred because it is possible to store a large amount of water in the protective layer, thereby exhibiting good proton mobility, and also to exhibit high acid resistance, thereby effectively preventing the erosion of the core material by the sulfonating agent.

[0022] Moreover, the membrane according to the present invention is required to have a resin membrane made of an ion exchange resin containing porous inorganic particles carrying a metal sulfide compound (hereinafter referred to as a metal sulfide compound carrier) laminated on the above-mentioned core material (sheet-shaped core material). The ion exchange resin (main matrix resin) containing the metal sulfide compound carrier is not particularly limited, and a polycondensate having an ion exchange group can be suitably used. For example, a polycondensate having a sulfonic acid group, a carboxylic acid group, a phosphonic acid group, a phosphinic acid group, or the like as a negatively charged ion exchange group, or a polycondensate having a pyridinium base, a quaternary ammonium base, a tertiary amine group, a phosphonium group, or the like as a positively charged (proton) ion exchange group can be used. Among them, a polycondensate having a sulfonic acid group is preferable because it can improve proton conductivity. Also, a polycondensate having a pyridinium base is preferable because it can improve proton selective permeability. In addition, as the ion exchange resin, one having a three-dimensional crosslinked structure can be used for the purpose of preventing swelling and deformation of the membrane.

[0023] Examples of such ion exchange resins include fluorine-based polymer electrolyte polymers, polyethersulfone resins, polyetheretherketone resins, phenol-formaldehyde resins, polystyrene resins, polytrifluorostyrene resins, trifluorostyrene resins, poly(2,3-diphenyl-1,4-phenylene oxide) resins, poly(aryl ether ketone) resins, poly(aryl ether sulfone) resins, poly(phenylquinoxane phosphorus) resins, poly(benzylsilane) resins, polystyrene-graft-ethylene tetrafluoroethylene resins, polystyrene-graft-polyvinylidene fluoride resins, polystyrene-graft-tetrafluoroethylene resins, polyimide resins, and polybenzimidazole resins, which are polymers having a hydrocarbon portion into which sulfonic acid groups or carboxylic acid groups have been introduced, lacquers, synthetic resins or natural resins having hydroxyl groups, rosin, shellac resins, and the like, which can be used alone or in combination of two or more. Among these, the use of rosin or shellac resin is preferable since it improves the proton conductivity (permeability) of the diaphragm, improves the chemical resistance, and improves the function of preventing leakage of the electrode liquid. It is particularly preferable to use a mixture of rosin and shellac resin.

[0024] Rosin used as an ion exchange resin is a residue remaining after collecting balsams such as pine resin, which is the sap of plants of the Pinaceae family, and distilling turpentine essential oil, and is a natural resin whose main components are rosin acids such as abietic acid, palustric acid, and isopimaric acid, and examples of such natural rosins include natural rosin, polymerized rosin, disproportionated rosin, hydrogenated rosin, reinforced rosin, rosin ester, and rosin metal salt. Natural rosins include gum rosin (obtained by filtering raw rosin extracted from the trunks of pine trees to remove impurities, then distilling it to separate turpentine oil with a low boiling point), tall rosin (obtained by rectifying crude tall oil recovered as tall oil in the craft process in which chemicals are added to pine wood chips and separated under high temperature and high pressure to extract pulp fibers), and wood rosin (obtained by extracting chip-like cut material of pine stumps after felling with a solvent and separating the solvent and turpentine oil). On the other hand, polymerized rosin is obtained by polymerizing natural rosin, and is a derivative containing dimerized resin acid derived from natural rosin. Disproportionated rosin is rosin that has been disproportionated from natural rosin, and hydrogenated rosin is rosin that has been hydrogenated to natural rosin and hydrogen has been added to the conjugated double bonds. Reinforced rosin is rosin that has been modified with unsaturated carboxylic acids such as fumaric acid, maleic anhydride, itaconic acid, acrylic acid, and methacrylic acid, and is obtained by reacting natural rosin with α,β-unsaturated carboxylic acid. Rosin esters are esters of various rosins including natural rosin, and rosin metal salts are natural rosin in which the hydrogen of the carboxyl group is replaced with a metal.

[0025] On the other hand, the shellac resin used as an ion exchange resin is a resin obtained by purifying the secretion (insect body covering) from the lac scale insect, and is an ester bond between aleuritic acid, which is an oxycarboxylic acid, and sesquiterpene such as jararic acid or lacsijaric acid. The shellac resin can be used alone, but it is preferable to use it mixed with various waxes (or dispersed in wax) because it improves the proton conductivity (passability). Examples of waxes include animal, vegetable, or petroleum waxes such as carnauba wax, paraffin wax, and microstalline wax, and these waxes can be used alone or in a mixture of two or more kinds. In addition, when the shellac resin is used mixed with a wax, it is preferable that the wax content is 5 to 50 mass % because the proton conductivity (passability) of the diaphragm is good, and it is particularly preferable that the wax content is 15 to 25 mass %. In addition, when using a mixture of rosin and shellac resin as the ion exchange resin, it is preferable to mix the shellac resin in an amount of 25 to 75 mass% of the total, as this provides good adhesion to the core material and brittleness, and it is even more preferable to mix the shellac resin in an amount of 40 to 60 mass%.

[0026] In addition, a surfactant can be added to the ion exchange resin for the purpose of maintaining the flexibility of the produced membrane at a high level for a long period of time. As the surfactant, various surfactants such as anionic surfactants, nonionic surfactants, amphoteric surfactants, and cationic surfactants can be suitably used. Among them, the use of linear alkylbenzenesulfonate sodium, such as sodium dodecylbenzenesulfonate, which is an ionic surfactant, is particularly preferred because it maintains the flexibility of the membrane at a high level for a long period of time when rosin and / or shellac resin is used as the main raw material of the ion exchange resin. The amount of surfactant added to the ion exchange resin is not particularly limited, but is preferably 0.5 to 5.0 mass% in terms of solid content ratio. If the amount of surfactant added is less than 0.5 mass%, it is not preferable because sufficient flexibility cannot be obtained after drying of the resin film, and conversely, if it exceeds 5.0 mass%, it is not preferable because it takes a long time to dry the resin film or the resin film becomes sticky after drying.

[0027] In addition, the above-mentioned ion exchange resin (main matrix resin) needs to contain porous inorganic granules carrying a metal sulfide compound (hereinafter, referred to as a metal sulfide compound carrier). The metal sulfide compound carrier is a porous inorganic granule carrying a metal sulfide compound obtained by reacting hot concentrated sulfuric acid with a metal. Hot concentrated sulfuric acid can be obtained by heating concentrated sulfuric acid at a temperature of 290°C to 300°C for about 20 to 40 minutes. In addition, as the metal to be reacted with hot concentrated sulfuric acid, copper, iron, gold, silver, aluminum, etc. can be used alone or in a mixture of two or more kinds. However, if the main component (80 mass% or more of the total metal) is gold or copper, the conductivity of the metal sulfide compound carrier is very good, which is preferable. Furthermore, if the main component (80 mass% or more of the total metal) is copper, it is particularly preferable because it can be manufactured inexpensively.

[0028] In addition, the porous inorganic granular material is preferably one having micropores to which ion exchange resin adheres, and porous inorganic granular materials or powders such as diatomaceous earth, sepiolite, zeolite, perlite, calcium silicate, kaolin, attapulgite, vermiculite, cristobalite, and silica can be preferably used. Among them, diatomaceous earth or sepiolite is more preferable because it improves the adsorption of ion exchange resin. Among diatomaceous earth, mesopore diatomaceous earth with a pore size of 2 to 50 nm is more preferably used because it has a larger specific surface area and micropore volume than general diatomaceous earth and improves the adsorption of ion exchange resin (adsorption into micropores). Furthermore, calcined mesopore diatomaceous earth, which is made by calcining this mesopore diatomaceous earth at approximately 800°C, is particularly suitable because the combustible impurities that had infiltrated into the micropores have disappeared, resulting in extremely good adsorption properties of ion exchange resins (adsorption properties into the micropores).

[0029] The metal sulfide compound support can be obtained by a production method having the following steps a and b. A mixing and heating process in which 30 to 70 parts by mass of hot concentrated sulfuric acid, 70 to 30 parts by mass of metal powder, and 5 to 50 parts by mass of fine powder of porous inorganic granular material such as diatomaceous earth are mixed and solidified by heating at a temperature of 190 to 210 ° C for a specified time. b. A crushing process in which the solidified material obtained by the mixing and heating process is crushed into fine powder particles.

[0030] In addition, the mixing ratio of hot concentrated sulfuric acid and metal powder in the mixing and heating step a is preferably 30-70 parts by mass: 70-30 parts by mass, since the oxidizing function of the obtained metal sulfide compound support is more durable, and is particularly preferably 40-60 parts by mass: 60-40 parts by mass. On the other hand, the mixing ratio of metal powder and porous inorganic granular material such as diatomaceous earth in the mixing and heating step a is preferably 70-30 parts by mass: 5-50 parts by mass, since the pulverization in the pulverization step c is easier, and is particularly preferably 60-40 parts by mass: 7-9 parts by mass.

[0031] The heating temperature in the above-mentioned mixing and heating step a is more preferably 190 to 210° C., since the metal sulfide compound-supported body functions as an oxidizing agent for a longer period of time, and is particularly preferably 195 to 205° C. The heating time required in the mixing and heating step a varies depending on the heating temperature, but when the heating temperature is about 180° C., it is preferably about 45 minutes to 1 hour, and when the heating temperature is 190 to 210° C., it is preferably about 20 minutes to 45 minutes.

[0032] In addition, the pulverization in the above-mentioned pulverization step b is preferably performed so that the average particle size of the solidified material obtained in the mixing and heating step a is 1.0 to 100 μm, since this improves the handleability when the metal sulfide compound support is mixed with an ion exchange resin (matrix resin), and it is more preferable to pulverize to 20 to 50 μm.

[0033] The amount of the metal sulfide compound support added to the ion exchange resin (main matrix resin) is not particularly limited, but an amount of 1 to 30 mass% is preferable because the adhesion of the ion exchange resin to the core material is maintained high and the proton conductivity (permeability) and selective permeability of the diaphragm are improved, more preferably 3 to 25 mass%, and particularly preferably 5 to 15 mass%.

[0034] In addition, the ion exchange resin (main matrix resin) can contain porous inorganic granules other than the above-mentioned metal sulfide compound carrier. As such porous inorganic granules, powders or granules of porous bodies such as diatomaceous earth, sepiolite, perlite, calcium silicate, kaolin, attapulgite, vermiculite, cristobalite, and other silica can be suitably used. Among them, the use of diatomaceous earth is more preferable because it further improves the adhesiveness of the ion exchange resin.

[0035] In addition, when laminating an ion exchange resin containing a metal sulfide compound carrier onto a core material (sheet-shaped core material) coated with a protective layer, a method can be suitably used in which the metal sulfide compound carrier is mixed and the matrix resin is sulfonated, and then the liquid mixed composition, that is, the ion exchange resin (i.e., a coating agent for forming a resin film), is applied to the core material, or the core material is impregnated with such a liquid ion exchange resin.

[0036] As a method for sulfonating the matrix resin while mixing the metal sulfide compound carrier, a method can be suitably used in which the matrix resin dissolved in a solvent (or dispersed in a dispersion medium) is sulfonated, and during the process, the metal sulfide compound carrier is added to the matrix resin solution (or dispersion liquid), stirred, and aged (left at room temperature (standing)) for a predetermined time, thereby allowing the matrix resin to be sufficiently adsorbed into the voids of the metal sulfide compound carrier. As an organic solvent or dispersion medium for dissolving (or dispersing) the matrix resin, alcohol, ether, acetic acid, glacial acetic acid, chloroform, benzene, etc. can be suitably used, and as a sulfonating agent for sulfonating the dissolved (or dispersed) matrix resin, concentrated sulfuric acid, hot concentrated sulfuric acid, fuming sulfuric acid, sulfur trioxide, chlorosulfonic acid, sulfamic acid, etc. can be suitably used.

[0037] In addition, as described above, when preparing a coating agent for forming a resin film, it is preferable to add 30 to 200 parts by mass of a solvent (or dispersion medium) and 5 to 100 parts by mass of a porous inorganic granular material (including a metal sulfide compound carrier) to 100 parts by mass of an ion exchange resin, and it is more preferable to set the amount (content) of the porous inorganic granular material to 10 to 70 parts by mass. If the amount of the porous inorganic granular material added is less than 5 parts by mass, the selective permeability of the protons of the diaphragm becomes poor, which is not preferable, and conversely, if the amount of the porous inorganic granular material added is more than 70 parts by mass, the resin film becomes easily peeled off from the core material, which is not preferable. In addition, it is preferable to add 5 to 30 parts by mass of a sulfonating agent such as hot concentrated sulfuric acid to 100 parts by mass of an ion exchange resin, and it is more preferable to add 10 to 30 parts by mass of the sulfonating agent. If the amount of sulfonating agent added is less than 5 parts by mass, the sulfonation is insufficient, which is not preferable, and conversely, if the amount of sulfonating agent added is more than 30 parts by mass, the resin membrane becomes brittle, which makes it difficult to prevent leakage of the electrode liquid, which is not preferable. In addition, it is also possible to add an emulsifier, a compatibilizer, a viscosity modifier, a heat stabilizer, an antioxidant, a surfactant, a crosslinking agent, a reaction accelerator, and other additives to the ion exchange resin as necessary. In addition, it is also possible to add titanium oxide, oxalic acid, formic acid, and the like to the ion exchange resin for the purpose of increasing the conductivity of the diaphragm. In particular, it is preferable to add titanium oxide to the ion exchange resin, since the added titanium oxide also functions as a reducing agent. In addition, adding titanium oxide to an ion exchange resin and leaving it to stand (stand still) for 72 hours or more is preferable because it improves the leveling properties when the ion exchange resin is laminated onto a core material (a sheet-like core material) by a method such as coating, making it less likely that unwanted irregularities will be formed on the coating surface, and the metal (copper, etc.) in the ion exchange resin will bleed out to the surface layer, further improving the conductivity of the diaphragm.

[0038] When the ion exchange resin (coating agent) is applied (laminated) to the core material by a method such as coating or impregnation, the application method can be suitably selected from the following methods: dip coating, knife coating, spraying coating, rotary screen coating, spread coating, roll coating, equilibrium rod coating, slush molding, rotational molding, cavity molding, etc. After the ion exchange resin (coating agent) is applied (laminated), the core material can be heated at a predetermined temperature to dry and solidify the liquid ion exchange resin, thereby increasing the adhesive strength of the ion exchange resin to the core material.

[0039] On the other hand, the thickness of the diaphragm according to the present invention is not particularly limited, but is preferably 5 to 200 μm, since the internal resistance value can be kept low to maintain high energy efficiency of the redox flow battery and short-circuiting of the electrolyte can be prevented, and is more preferably 5 to 50 μm, and particularly preferably 5 to 20 μm.

[0040] Furthermore, the membrane according to the present invention can also have a coating made of a hydrophobic or water-resistant synthetic resin between the protective layer covering the sheet-like core material and the resin membrane (resin membrane made of an ion exchange resin). By forming such a coating (i.e., covering the protective layer covering the sheet-like core material with a coating made of a hydrophobic or water-resistant synthetic resin), it is possible to effectively prevent the protective layer from leaking (dissolving) into the electrolyte. As the hydrophobic or water-resistant synthetic resin used to form such a coating, synthetic resins such as acrylic, epoxy, polyethylene, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polydimethylsiloxane, polyester, polyurethane, and natural resins can be suitably used, but the use of rosin (natural rosin, polymerized rosin, etc.) is preferable because it can more effectively prevent the protective layer from leaking (dissolving) into the electrolyte. Furthermore, it is preferable to include the above-mentioned metal sulfide compound carrier or metal sulfide compound in the material forming such a coating, because the proton conductivity (permeability) of the membrane is improved.

[0041] The diaphragm according to the present invention having the above-mentioned structure is used as a member for separating two types of electrolytes in a redox flow battery using iron ions and chromium ions and a redox flow battery utilizing the oxidation-reduction action of vanadium, and is particularly suitable for use as a diaphragm in a vanadium-based redox flow battery utilizing the oxidation-reduction action of vanadium.

[0042] FIG. 1 shows an example of a redox flow battery in which the diaphragm according to the present invention is used. The redox flow battery R includes two cell stacks 6, 6 each formed by stacking a plurality of (four) cells 5, 5, etc., a positive electrode liquid (vanadium V 4+ etc.), a positive electrode liquid tank 9a storing negative electrode liquid (vanadium V 3+The cell stack is made up of a negative electrode liquid tank 9b that stores the positive electrode liquid, a positive electrode pump 10a for circulating the positive electrode liquid, a negative electrode pump 10b for circulating the negative electrode liquid, and an AC / DC converter 11. In Fig. 1, the lines connecting the cell stack, the positive electrode liquid tank, the AC / DC converter, etc. indicate paths for the electrolyte or electrical circuits.

[0043] FIG. 2 shows the cells 5 constituting each of the cell stacks 6, 6. Each of the cells 5, 5·· has a structure in which a diaphragm 1 is sandwiched between a positive electrode frame 3a having a positive electrode 2a and a negative electrode frame 3b having a negative electrode 2b. The positive electrode frame 3a is provided with an inlet 7a and an outlet 8a for the positive electrode fluid, and the negative electrode frame 3b is provided with an inlet 7b and an outlet 8b for the negative electrode fluid. In the two cell stacks 6, 6, the inlets 7a, 7a·· on the positive electrode frame 3a side of each of the cells 5, 5·· are connected to each other by pipes, and these pipes are connected to a positive electrode fluid tank 9a via a positive electrode pump 10a. Furthermore, the outlets 8a, 8a·· on the positive electrode frame 3a side are connected to each other by pipes, and these pipes are connected to the positive electrode fluid tank 9a. Meanwhile, the intake ports 7b, 7b on the negative electrode frame 3b side of each cell 5, 5... are connected to each other by pipes, and these pipes are connected to the negative electrode liquid tank 9b via the negative electrode pump 10b. Furthermore, the exhaust ports 8b, 8b... on the negative electrode frame 3b side are connected to each other by pipes, and these pipes are connected to the negative electrode liquid tank 9b.

[0044] The redox flow battery R configured as described above can repeatedly be charged and discharged by operating the positive electrode pump 10a and the negative electrode pump 10b to circulate the positive and negative electrode fluids through the cells 5, 5... of each cell stack 6, 6, the positive electrode fluid tank 9a, and the negative electrode fluid tank 9b. EXAMPLES

[0045] The diaphragm according to the present invention and its manufacturing method will be described in detail below with reference to examples and comparative examples, but the diaphragm according to the present invention and its manufacturing method are not limited to the embodiments of the examples, and can be appropriately modified as necessary without departing from the spirit of the present invention. The methods for evaluating the properties in the examples and comparative examples are as follows.

[0046] <Proton Conductivity> The membranes (immediately after preparation) obtained in the examples and comparative examples were installed as the membranes of the redox flow battery R as shown in FIG. 1 (membrane 1), and the pump 10 was operated to sufficiently wet the membrane 1 with the electrolyte, and a voltage was applied between the electrodes via an AC-DC converter to evaluate the state of electrolytic reduction based on the change in color of the electrolyte. That is, when a tetravalent vanadium electrolyte was injected into each of the positive electrode electrolyte tank 9a and the negative electrode electrolyte tank 9b to perform initial charging, when electrolytic reduction begins, vanadium is oxidized from tetravalent (blue) to pentavalent (reddish yellow) at the positive electrode, and reduced from tetravalent (blue) to trivalent (blue-green) to divalent (blackish green) at the negative electrode. Therefore, it is possible to judge whether electrolytic reduction is being performed properly (i.e., whether proton conduction is being performed properly) based on the change in color of the vanadium electrolyte. Therefore, the color change of the vanadium electrolyte before and after the initial charging was visually evaluated in the following three stages. ○ The color of the electrolyte has changed sufficiently (completely) △: The color change of the electrolyte was insufficient. × The color of the electrolyte did not change

[0047] <Handling> The membranes obtained in the examples and comparative examples were dried at room temperature for 72 hours, and then the "proton conductivity" was evaluated by the method described above. The color change of the vanadium electrolyte before and after the first charge was visually evaluated on the following three-point scale (i.e., whether or not proton conductivity was exhibited even after drying was used as an index of handleability). ○ The color of the electrolyte has changed sufficiently (completely) △: The color change of the electrolyte was insufficient. × The color of the electrolyte did not change

[0048] <Internal resistance (AC impedance)> Measuring equipment: A fuel cell evaluation system (Chino FC5100 series) and an attached potentio / galvanostat (AUTO LAB PGSTAT302) were used to measure the AC impedance of the redox flow battery membranes obtained in the examples and comparative examples (the membrane width was 0.5 cm, and the electrode distance was 0.5 cm). The AC impedance was measured and evaluated according to the following criteria. ○ AC impedance is less than 0.3 S / cm × AC impedance is 0.3S / cm or more

[0049] <Prevention of electrolyte leakage between membranes (change in electrolyte color)> When the proton conductivity was evaluated as described above, the leakage of the electrolyte between the membranes was checked, the rotation direction of the pump was reversed, and the pressure of the positive and negative electrolytes was set at 1:3. After operation for 24 hours, the color change of both electrolytes was visually evaluated according to the following criteria. No change in the color of the electrolyte was observed. △: A slight change in the color of the electrolyte was observed. ×: A change in the color of the electrolyte was observed.

[0050] <Durability> As in the evaluation of "proton conductivity" described above, the diaphragms obtained in the Examples and Comparative Examples (immediately after production) were installed as diaphragms in the redox flow battery R shown in FIG. 1 (diaphragm 1), and after 30 charge-discharge cycles, the diaphragms were taken out and the surface conditions were visually evaluated according to the following three-level scale. ○ No damage was observed on the membrane surface. △: Slight damage to the membrane was observed × Damage to the membrane surface was observed

[0051] In some examples, copper sulfide compound supports A to E and zinc sulfide compound supports obtained by the following manufacturing methods were used as metal sulfide compound supports (porous inorganic granules supporting a metal sulfide compound). The compositions and manufacturing methods of the copper sulfide compound supports A to E and zinc sulfide compound supports are shown in Table 2. <Copper sulfide compound support A> Hot concentrated sulfuric acid was obtained by heating concentrated sulfuric acid at a temperature of 295°C for about 30 minutes. Then, 30 parts by mass of the hot concentrated sulfuric acid and 50 parts by mass of copper powder (average particle size = about 30 μm) were mixed and thoroughly stirred. Thereafter, the mixed composition was heated at a temperature of 200°C for 30 minutes (hot concentrated sulfuric acid turned red), and 8.0 parts by mass of diatomaceous earth fine powder (calcined at a temperature of 800°C and in a fine powder form with an average particle size of 10 μm) was added to the mixed composition immediately after heating and mixed to obtain a solidified material. Furthermore, the solidified material (soybean-like coarse granules) was cooled at room temperature and then pulverized using a pulverizer to an average particle size of about 10 μm (particle size distribution: 2 to 30 μm) to obtain a copper sulfide compound support A in the form of fine powder.

[0052] <Copper sulfide compound support B> 50 parts by mass of hot concentrated sulfuric acid obtained in the same manner as in the production of copper sulfide compound support A and 50 parts by mass of copper powder (average particle size = about 30 μm) were mixed and thoroughly stirred. Thereafter, the mixed composition was heated at a temperature of 200 ° C for 30 minutes (hot concentrated sulfuric acid turned red), and 20.0 parts by mass of diatomaceous earth fine powder (calcined at a temperature of 800 ° C and in the form of a fine powder with an average particle size of 10 μm) was added to the mixed composition immediately after heating and mixed to obtain a solidified material. Furthermore, the solidified material (soybean-like coarse granules) was cooled at room temperature and then pulverized using a pulverizer to an average particle size of about 10 μm (particle size distribution: 2 to 30 μm) to obtain copper sulfide compound support B.

[0053] <Copper sulfide compound support C> 50 parts by mass of hot concentrated sulfuric acid obtained in the same manner as in the production of copper sulfide compound support A and 50 parts by mass of copper powder (average particle size = about 30 μm) were mixed and thoroughly stirred. Thereafter, the mixed composition was heated at a temperature of 200 ° C for 30 minutes (hot concentrated sulfuric acid turned red), and 12.5 parts by mass of diatomaceous earth fine powder (calcined at a temperature of 800 ° C and in the form of a fine powder with an average particle size of 10 μm) was added to the mixed composition immediately after heating and mixed to obtain a solidified material. Furthermore, the solidified material (soybean-like coarse granules) was cooled at room temperature and then pulverized using a pulverizer to an average particle size of about 10 μm (particle size distribution: 2 to 30 μm) to obtain copper sulfide compound support C.

[0054] <Copper sulfide compound support D> 50 parts by mass of hot concentrated sulfuric acid obtained in the same manner as in the production of copper sulfide compound support A, 50 parts by mass of copper powder, and 12.5 parts by mass of diatomaceous earth fine powder (the same as that used in the production of copper sulfide compound support A) were mixed with stirring and heated at a temperature of 200° C. for 30 minutes. Thereafter, the obtained solidified material (soybean-like coarse granules) was pulverized in the same manner as in Example 1 to an average particle size of about 10 μm (particle size distribution: 2 to 30 μm), thereby obtaining copper sulfide compound support D.

[0055] <Copper sulfide compound support E> 40 parts by mass of hot concentrated sulfuric acid obtained in the same manner as in the production of copper sulfide compound support A, 50 parts by mass of copper powder, and 25 parts by mass of diatomaceous earth fine powder (the same as that used in the production of copper sulfide compound support A) were mixed with stirring and heated at a temperature of 200° C. for 30 minutes. Thereafter, the obtained solidified material (soybean-like coarse granules) was pulverized in the same manner as in the production of copper sulfide compound support A to an average particle size of about 10 μm (particle size distribution: 2 to 30 μm), thereby obtaining copper sulfide compound support E.

[0056] <Zinc sulfide compound support> Hot concentrated sulfuric acid was obtained by heating concentrated sulfuric acid at a temperature of 295°C for about 30 minutes. Then, 30 parts by mass of the hot concentrated sulfuric acid and 50 parts by mass of zinc powder (average particle size = about 30 μm) were mixed and thoroughly stirred. Thereafter, the mixed composition was heated at a temperature of 200°C for 30 minutes (hot concentrated sulfuric acid turned red), and 8.0 parts by mass of diatomaceous earth fine powder (calcined at a temperature of 800°C and in a fine powder form with an average particle size of 10 μm) was added to the mixed composition immediately after heating and mixed to obtain a solidified material. Furthermore, the solidified material (soybean-like coarse granular material) was cooled at room temperature and then pulverized using a pulverizer to an average particle size of about 10 μm (particle size distribution: 2 to 30 μm) to obtain a zinc sulfide compound support in a fine powder form.

[0057] [Example 1] <Preparation of coating solution> A liquid composition (first agent) for a coating liquid was prepared by mixing rosins (gum rosin and polymerized rosin), acetic acid (solvent), diatomaceous earth (average particle size 5-10 μm), and hot concentrated sulfuric acid in the following ratio. That is, 120 parts by mass of rosins consisting of gum rosin (100 parts by mass) and polymerized rosin (20 parts by mass) were added with the same amount of acetic acid (solvent), left to stand for 72 hours (about 120 hours) to allow natural dissolution, and then the naturally dissolved solution was stirred and mixed with a mixer to prepare a rosin solution. Then, 25 parts by mass of diatomaceous earth and 3.5 parts by mass of hot concentrated sulfuric acid (sulfonating agent) were added to the rosin solution, stirred, and then allowed to stand for about 24 hours (about 120 hours) to obtain a liquid composition (first agent) for a coating liquid. First agent for coating liquid (unit: part by mass) a. Rosins (gum rosin / polymerized rosin) 220.0 b.Acetic acid 120.0 c. Diatomaceous earth (average particle size 5-10 μm) 25.0 d. Hot concentrated sulfuric acid (sulfonating agent) 3.5

[0058] On the other hand, a composition (second agent) for a coating liquid was prepared by mixing 1,5-dichloroanthraquinone, the above-mentioned copper sulfide compound support A, titanium oxide, and a surfactant, sodium dodecylbenzenesulfonate (hard type), in the following ratio. ·Second agent for coating liquid e.1,5-dichloroanthraquinone 2.0 f. Metal sulfide compound support 35.0 g. Titanium dioxide 15.0 h.Surfactant (sodium dodecylbenzenesulfonate) 2.0

[0059] The first agent for the coating liquid (about 368.5 parts by mass) and the second agent for the coating liquid (about 54 parts by mass) were thoroughly mixed and stirred, and allowed to stand for about 48 hours to obtain a coating liquid.

[0060] <Preparation of core material> Polyethylene terephthalate (PET) basis weight: 70g / m 2 A long porous sheet with a constant width and a thickness of 0.23 mm was impregnated with an acrylic water-absorbing resin (a water dispersion of unneutralized polyacrylic acid, with a solid content concentration of 15 to 16% by mass). After that, the PET porous sheet containing the acrylic water-absorbing resin was passed between pressure rolls to remove excess acrylic water-absorbing resin, and then dried for about 10 minutes in an atmosphere at 100°C. The process of "impregnation → removal of excess acrylic water-absorbing resin → drying" was repeated three times to obtain a core material made of a PET porous sheet with a protective film of acrylic water-absorbing resin formed on the surface. The amount of acrylic water-absorbing resin applied to the core material (impregnation amount) was about 200 g / m 2 It was.

[0061] <Application of coating liquid> The above-mentioned coating liquid was applied to the surface of the core material obtained as described above (made of PET nonwoven fabric with a protective film of acrylic water-absorbent resin formed on the surface) by gravure coating. The coating amount was 350 g / m 2The core material coated with the coating liquid was then naturally dried for about 24 hours and then heat-treated for about 3.0 hours in an atmosphere at about 150°C to sulfonate the rosins, thereby obtaining a diaphragm of Example 1 having a rosin ion-exchange resin layer (resin membrane) formed on the surface. The proton conductivity, handling properties, electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Example 1 were evaluated by the above-mentioned methods. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0062] [Example 2] <Preparation of coating solution> A liquid composition (first agent) for a coating liquid was prepared by mixing the same rosins as in Example 1, acetic acid (solvent), the same diatomaceous earth as in Example 1, and hot concentrated sulfuric acid in the following ratio. That is, a rosin solution was prepared by adding the same amount of acetic acid (solvent) to 120 parts by mass of rosins consisting of gum rosin (100 parts by mass) and polymerized rosin (20 parts by mass) and stirring and mixing with a mixer. Thereafter, 25 parts by mass of diatomaceous earth and 3.5 parts by mass of hot concentrated sulfuric acid (sulfonating agent) were added to the rosin solution and stirred, and then the mixture was left to stand for about 24 hours to obtain a liquid composition (first agent) for a coating liquid. First agent for coating liquid (unit: part by mass) a. Rosins (gum rosin / polymerized rosin) 120.0 b.Acetic acid 120.0 c. Diatomaceous earth (average particle size 5-10 μm) 25.0 d. Hot concentrated sulfuric acid (sulfonating agent) 3.5

[0063] On the other hand, a composition for a coating liquid (second agent) was prepared by mixing 1,5-dichloroanthraquinone, the above-mentioned copper sulfide compound support A, titanium oxide, sodium dodecylbenzenesulfonate (hard type) as a surfactant, and shellac resin (containing 10% by mass of wax made of carnauba wax) in the following ratio. Second agent for coating liquid (unit: part by mass) e.1,5-dichloroanthraquinone 2.0 f. Metal sulfide compound support 35.0 g. Titanium dioxide 15.0 h.Surfactant (sodium dodecylbenzenesulfonate) 2.0 i. Shellac resin (containing 20% ​​wax by mass) 100.0

[0064] The first agent for the coating solution (about 268.5 parts by mass) and the second agent for the coating solution (about 154 parts by mass) were thoroughly mixed and stirred, and the mixture was left to stand for about 48 hours to obtain a coating solution. The resulting coating solution was then applied to the surface of a core material (made of a PET nonwoven fabric having a protective film of an acrylic water-absorbing resin formed on the surface) obtained in the same manner as in Example 1, and the core material was naturally dried, and then the rosins and shellac resin were sulfonated to obtain a diaphragm of Example 2 having an ion-exchange resin layer of rosins and shellac resin formed on the surface. The proton conductivity, handling properties, electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Example 2 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0065] [Example 3] A diaphragm of Example 3 having an ion exchange resin layer of rosins and shellac resin formed on the surface was obtained in the same manner as in Example 2, except that the shellac resin was changed to one containing 20 mass% of wax made of carnauba wax when preparing the coating liquid. The proton conductivity, handleability, electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Example 3 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0066] [Examples 4 to 8] Diaphragms of Examples 4 to 8 having ion exchange resin layers of rosin and shellac resin formed on the surface were obtained in the same manner as in Example 3, except that in preparing the coating liquid, the porous inorganic granules supporting a metal sulfide compound were changed to copper sulfide compound supports B to E and zinc sulfide compound supports, respectively. The proton conductivity, handleability, electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragms of Examples 4 to 8 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0067] [Example 9] <Preparation of second agent for coating liquid> A composition for a coating liquid (second agent) was prepared by mixing 1,5-dichloroanthraquinone, the above-mentioned copper sulfide compound support A, titanium oxide, and a surfactant, sodium dodecylbenzenesulfonate (hard type), in the following ratio. Second agent for coating liquid (unit: part by mass) e.1,5-dichloroanthraquinone 2.0 f. Metal sulfide compound support 20.0 g. Titanium dioxide 30.0 h.Surfactant (sodium dodecylbenzenesulfonate) 2.0 i. Shellac resin (containing 20% ​​wax by mass) 100.0

[0068] A diaphragm of Example 9 having an ion exchange resin layer of rosins and shellac resin formed on the surface was obtained in the same manner as in Example 3, except that the second agent for the coating liquid prepared as above was used. The proton conductivity, handling properties, electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Example 9 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0069] [Example 10] A diaphragm of Example 10 having an ion exchange resin layer of rosins and shellac resin formed on the surface was obtained in the same manner as in Example 2, except that the shellac resin was changed to one containing 30 mass% of wax made of carnauba wax when preparing the coating liquid. The proton conductivity, handling properties, electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Example 10 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0070] [Example 11] <Preparation of coating solution> Acetic acid (solvent), diatomaceous earth the same as in Example 1, hot concentrated sulfuric acid, 1,5-dichloroanthraquinone, copper sulfide compound support A, titanium oxide, sodium dodecyl benzoate (hard type), and shellac resin the same as in Example 3 (containing 20% ​​by mass of wax made of carnauba wax) were mixed in the following ratio to prepare a coating liquid. That is, 120 parts by mass of acetic acid (solvent) was added to 220 parts by mass of shellac resin and stirred and mixed with a mixer to prepare a shellac resin solution. Thereafter, 25 parts by mass of diatomaceous earth and 3.5 parts by mass of hot concentrated sulfuric acid (sulfonating agent) were added to the shellac resin solution, stirred, and then allowed to stand for about 24 hours. Furthermore, 2 parts by mass of 1,5-dichloroanthraquinone, 35 parts by mass of copper sulfide compound support A, 15 parts by mass of titanium oxide, and 2 parts by mass of sodium dodecyl benzoate (hard type) were added to the mixed composition, thoroughly mixed and stirred, and allowed to stand for about 48 hours to obtain a coating liquid. First agent for coating liquid (unit: part by mass) b.Acetic acid 120.0 c. Diatomaceous earth (average particle size 5-10 μm) 25.0 d. Hot concentrated sulfuric acid (sulfonating agent) 3.5 e.1,5-dichloroanthraquinone 2.0 f. Metal sulfide compound support 35.0 g. Titanium dioxide 15.0 h.Surfactant (sodium dodecylbenzenesulfonate) 2.0 i. Shellac resin (containing 20% ​​wax by mass) 220.0

[0071] The obtained coating liquid was applied to the surface of a core material (made of a PET nonwoven fabric having a protective film of an acrylic water-absorbent resin formed on its surface) obtained in the same manner as in Example 1, and then the core material was naturally dried, and the shellac resin was sulfonated to obtain a diaphragm of Example 10 having an ion-exchange resin layer of shellac resin formed on its surface. The proton conductivity, handling properties, electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Example 10 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0072] [Example 12] <Preparation of coating solution> A coating liquid was prepared by mixing acetic acid (solvent), the same diatomaceous earth as in Example 1, hot concentrated sulfuric acid, 1,5-dichloroanthraquinone, copper sulfide compound support A, titanium oxide, sodium dodecyl benzoate (hard type), and cellulose in the following ratio. That is, a cellulose resin solution was prepared by adding 120 parts by mass of acetic acid (solvent) to 220 parts by mass of cellulose and stirring and mixing with a mixer. Thereafter, 25 parts by mass of diatomaceous earth and 3.5 parts by mass of hot concentrated sulfuric acid (sulfonating agent) were added to the cellulose resin solution, stirred, and then allowed to stand for about 24 hours. Furthermore, 2 parts by mass of 1,5-dichloroanthraquinone, 35 parts by mass of copper sulfide compound support A, 15 parts by mass of titanium oxide, and 2 parts by mass of sodium dodecyl benzoate (hard type) were added to the mixed composition, thoroughly mixed and stirred, and allowed to stand for about 48 hours to obtain a coating liquid. First agent for coating liquid (unit: part by mass) b.Acetic acid 120.0 c. Diatomaceous earth (average particle size 5-10 μm) 25.0 d. Hot concentrated sulfuric acid (sulfonating agent) 3.5 e.1,5-dichloroanthraquinone 2.0 f. Metal sulfide compound support 35.0 g. Titanium dioxide 15.0 h.Surfactant (sodium dodecylbenzenesulfonate) 2.0 i. Cellulose 220.0

[0073] The obtained coating liquid was applied to the surface of a core material (made of a PET nonwoven fabric having a protective film of an acrylic water-absorbent resin formed on its surface) obtained in the same manner as in Example 1, and then the core material was naturally dried, and the cellulose was sulfonated to obtain a diaphragm of Example 11 having a cellulose ion-exchange resin layer formed on its surface. The proton conductivity, handleability, electrode electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Example 11 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0074] [Example 13] Core material is polypropylene (PP) with a basis weight of 48g / m 2 A diaphragm of Example 13 having an ion exchange resin layer of rosins and shellac resin formed on the surface was obtained in the same manner as in Example 3, except that the diaphragm was changed to a long porous sheet of a constant width having a thickness of 1.0 mm. The proton conductivity, handleability, electrode electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Example 13 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0075] [Example 14] A diaphragm of Example 14 having an ion exchange resin layer of rosins and shellac resin formed on the surface was obtained in the same manner as in Example 3, except that a nonwoven fabric sheet made of PET similar to that in Example 1 was impregnated in an aqueous dispersion of urethane resin (solid content concentration = 15 to 16 mass%) to form a protective film of urethane resin on the surface of the core material when preparing the core material. The proton conductivity, handling properties, electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Example 14 were evaluated by the same methods as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0076] [Example 15] <Preparation of second agent for coating liquid> A composition for a coating liquid (second agent) was prepared by mixing 1,5-dichloroanthraquinone, the above-mentioned copper sulfide compound support A, titanium oxide, and a surfactant, sodium dodecylbenzenesulfonate (hard type), in the following ratio. Second agent for coating liquid (unit: part by mass) e.1,5-dichloroanthraquinone 2.0 f. Metal sulfide compound support 45.0 g. Titanium dioxide 5.0 h.Surfactant (sodium dodecylbenzenesulfonate) 2.0 i. Shellac resin (containing 20% ​​wax by mass) 100.0

[0077] A diaphragm of Example 15 having an ion exchange resin layer of rosins and shellac resin formed on the surface was obtained in the same manner as in Example 3, except that the second agent for the coating liquid prepared as above was used. The proton conductivity, handling properties, electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Example 15 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0078] [Example 16] <Preparation of coating solution for intermediate film formation> A coating liquid for forming a hydrophobic intermediate coating (covering the protective layer that covers the core material) was prepared by mixing the same rosins, acetic acid (solvent), and metal sulfide compound support A as in Example 1 in the following ratio: That is, the same amount of acetic acid and metal sulfide compound support A were added to 120 parts by mass of rosins consisting of gum rosin (100 parts by mass) and polymerized rosin (20 parts by mass), and the mixture was stirred and mixed in a mixer to obtain a coating liquid for forming an intermediate coating. Rosins (gum rosin / polymerized rosin) 120.0 Acetic acid 120.0 Metal sulfide compound support 2.0

[0079] The above-mentioned coating solution for forming the intermediate film was applied by gravure coating to the surface of the core material obtained by the same method as in Example 1 (i.e., the core material made of PET nonwoven fabric having a protective film made of acrylic water-absorbent resin formed on the surface). The coating amount was 175 g / m 2 The core material to which the coating liquid had been applied was then allowed to air dry for about 24 hours. A coating liquid for forming a resin film similar to that in Example 1 was then applied to the surface of the core material formed by laminating the protective film and intermediate coating film in the same manner as in Example 1, and the core material was then dried and heated to obtain a diaphragm of Example 16 having a rosin ion exchange resin layer (resin film) formed on the surface. FIG. 3 shows a cross section of the diaphragm of Example 16 obtained, and in diaphragm 1, a protective layer Lp, intermediate coating Lb, and resin film Li are laminated on a core material B.

[0080] The proton conductivity, handling properties, electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Example 16 were evaluated by the above-mentioned methods. The evaluation results are shown in Table 1 together with the configuration of the diaphragm. The obtained diaphragm of Example 16 was stored at room temperature (about 25°C) for three months, and sufficient flexibility was maintained. Furthermore, the proton conductivity, handling properties, electrolyte leakage prevention function, internal resistance, and durability of the diaphragm after the three-month storage were evaluated by the above-mentioned methods, and the evaluation results were equivalent to those immediately after production.

[0081] [Comparative Example 1] <Preparation of second agent for coating liquid> A composition for a coating liquid (second agent) was prepared by mixing 1,5-dichloroanthraquinone, titanium oxide, and a surfactant, sodium dodecylbenzenesulfonate (hard type), in the ratio shown below. ·Second agent for coating liquid e.1,5-dichloroanthraquinone 2.0 g. Titanium dioxide 50.0 h.Surfactant (sodium dodecylbenzenesulfonate) 2.0

[0082] A diaphragm of Comparative Example 1 having a rosin ion exchange resin layer formed on the surface was obtained in the same manner as in Example 1, except that the second agent for the coating liquid prepared as above was used. The proton conductivity, handling properties, electrode electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Comparative Example 1 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0083] [Comparative Example 2] <Preparation of second agent for coating liquid> As in Comparative Example 1, 1,5-dichloroanthraquinone, titanium oxide, and sodium dodecylbenzenesulfonate (hard type) as a surfactant were mixed in the following ratio to prepare a composition (second agent) for a coating liquid. ·Second agent for coating liquid e.1,5-dichloroanthraquinone 2.0 g. Titanium dioxide 50.0 h.Surfactant (sodium dodecylbenzenesulfonate) 2.0

[0084] A coating liquid was obtained in the same manner as in Example 1, except that the second agent for the coating liquid prepared as above was used. The coating liquid was then applied to the surface of the same core material as in Example 13 (a PP nonwoven fabric having a protective film of an acrylic water-absorbent resin formed on the surface) in the same manner as in Example 1, and the resulting core material was naturally dried, and the rosins were then sulfonated to obtain a diaphragm of Comparative Example 2 having a rosin ion-exchange resin layer formed on the surface. The proton conductivity, handling properties, electrolyte leakage prevention function, internal resistance, and durability of the obtained diaphragm of Comparative Example 2 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1 together with the configuration of the diaphragm.

[0085] [Table 1]

[0086] [Table 2]

[0087] It can be seen from Table 1 that the diaphragms of Examples 1 to 16 have good proton conductivity, handleability, and electrolyte leakage prevention function, low internal resistance, and excellent durability. In contrast, the diaphragms of Comparative Examples 1 and 2 have good proton conductivity, electrolyte leakage prevention function, and excellent durability, but poor handleability and high internal resistance. [Industrial Applicability]

[0088] Since the diaphragm according to the present invention has excellent effects as described above, it can be suitably used as a member for isolating an electrode solution in a redox flow battery, particularly a vanadium-based redox flow battery. [Explanation of symbols]

[0089] 1...diaphragm 2...electrode 2a...Positive electrode 2b...Negative electrode 3. Frame 3a Positive electrode frame 3b Negative electrode frame 4. Bipolar plate 4a Positive bipolar plate 4b Negative bipolar plate 5 Cell 6. Cell stack 7...Suction and discharge port 7a · Positive electrode liquid suction and discharge port 7b··Negative electrode liquid suction and discharge port 8 · Suction and discharge port 8a · Positive electrode liquid suction and discharge port 8b··Negative electrode liquid suction and discharge port 9. Electrolyte tank 9a Positive electrolyte tank 9b Negative electrolyte tank 10a ·· Positive electrolyte pump, 10b Negative electrolyte pump B Core material Lp...protective layer Lb...Intermediate film Li··Resin film

Claims

1. A membrane for use in a redox flow battery, comprising: A redox flow battery membrane comprising a sheet-like core material and a resin membrane made of an ion exchange resin containing porous inorganic granules carrying a metal sulfide compound laminated on the outside of the sheet-like core material.

2. 2. The redox flow battery membrane according to claim 1, wherein the ion exchange resin contains at least one of rosin or a modified product thereof, shellac resin, viscose, and cellulose.

3. 2. The redox flow battery separator according to claim 1, wherein the sheet-like core material is coated with a protective layer mainly composed of an acrylic water-absorbing polymer, and the resin film is laminated on the protective layer.

4. 2. The redox flow battery membrane according to claim 1, further comprising an intermediate film made of a hydrophobic or water-resistant synthetic resin between the protective layer and the resin film.

5. 2. The redox flow battery membrane according to claim 1, wherein a surfactant is added to the ion exchange resin.

6. A method for producing a membrane for a redox flow battery, comprising the steps of: A step of covering the sheet-like core material with a protective layer; and adhering an ion exchange resin containing porous inorganic granules supporting a metal sulfide compound to a sheet-like core material covered with a protective layer.

Citation Information

Patent Citations

  • Redox flow battery

    JP1987226580A

  • Redox battery

    JP1994188005A

  • Redox cell

    JP2005158383A

Cited By

  • Composite diaphragm, preparation method thereof and battery

    CN121123573A

  • Composite separator and its preparation method and battery

    CN121123573B